Advertising, gender and society a psychological perspective - Riley, Magdalena Zawisza- (Routledge, 2019)
"Advertising, Gender and Society explores contemporary social-psychological theory and original research that examines the portrayal of gender in advertising. It reports empirical data, discusses the social implications of gendered advertising and comments on the relevant 2019 Advertising Standards Authority rules. Zawisza-Riley analyses theories such as stereotype content and elaboration likelihood models, stereotype threat and ambivalent sexism theories, the selectivity hypothesis as well as implicit and embodied cognition to illuminate the relationships between sex, gender and advertising in cultural and social contexts. The author thus examines the portrayal of gender in advertising, its effectiveness and effect on audiences and the ways in which audiences, marketers and policy-makers can mitigate potential harm of gendered advertising. She offers theory extension and novel application of existing theory and research to the subject of gender advertising. Advertising, Gender and Society is ideal for students, academics and professionals in the fields of psychology, gender and media studies as well as marketing, advertising and policy-making."-- Back cover.